Disruption of Healthcare in New York City During the COVID-19 Pandemic: Findings From Residents Living in North and Central Brooklyn, the South Bronx, and East and Central Harlem - Sheena Dorvil; Christina Nieves; Jennifer Pierre; Jocelyn Valdez; Rachel Dannefer; Lauren J. Shiman; Fatoumata Diallo (SAGE Publishing, 2023)
Introduction: The COVID-19 pandemic has disproportionately affected some New York City (NYC) neighborhoods that primarily consist of Black, Indigenous, and Latinx residents. In comparison to the rest of NYC, these neighborhoods experienced high hospitalization and COVID-related death rates, which has been attributed to a longstanding history of structural racism and disinvestment. While stay-at-home orders were implemented to reduce the spread of COVID-19, this may have also affected access and utilization of non-COVID related healthcare services. This study aims to assess the prevalence of and reasons for the disruption of non-COVID related healthcare services during the first 18 months of the pandemic. Methods: From September 30, 2021 to November 4, 2021, the NYC Health Department administered the COVID-19 Community Recovery Survey to a subset of residents who were part of the NYC Health Panel a probability-based survey panel. This cross-sectional survey, which included closed and open-ended questions, was either self-administered online or completed via CATI (Computer Assisted Telephone Interviewing) in English, Spanish, and Simplified Chinese. Descriptive statistics were used to summarize responses and unweighted, weighted, age-adjusted percentages, and 95% Confidence Intervals (CIs) were calculated. Results: With a response rate of 30.3% (N = 1358), more than half of participants (54%) reported disruption to either routine physical healthcare or mental health services. Concern about getting COVID-19 (61%), stay-at-home policies (40%), belief that care could safely be postponed (35%), and appointment challenges (34%) were among reasons for delaying routine healthcare. Concern about getting COVID-19 (38%) and reduced hours of service (36%) were primary reasons for delaying mental healthcare. Reported reasons for the sustained delay of care past 18 months involved COVID concerns, appointment, and insurance challenges. Conclusions: Due to the pandemic, some disruption to healthcare was expected. However, most study participants either avoided or experienced a delay in healthcare. The delay of non-COVID related healthcare throughout the pandemic may result in the further widening of the health inequity gap among NYC residents dealing with a higher chronic disease burden before the start of the COVID-19 pandemic in March 2020. Findings from this study can support equitable COVID-19 recovery, and guide efforts with health promotion.